Presensi Pengunjung Resource Center Berbasis J2SE - Norhikmah, Norhikmah (JURIKOM (Jurnal Riset Komputer), 2018)
Recording attendance in an institution is absolutely necessary, recording can be used as an evaluation material for the institution, including educational institutions, especially the end of the data section that comes to library, storing visitor data in order to find out how many people visit the library both internal and external visitors , for the presence of external visitors not only reports how many people come but also can know from which agency and the need to visit. The report data can be a material consideration for adding collections and others. Visitor attendance information system made through the analysis process of Performance, Information, Economics, Control, Efficiency, and Service, the output of this study is a visitor presence application for students and visitors from outside by applying the concept of data access oriented or abbreviated as DAO desktop-based which is where the DAO concept divides objects into several classes, namely classes for models, implementations, interfaces and views.